2020
DOI: 10.32794/mr11250051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of melatonin effects on toxicology of vesicant chemical warfare agents: When science meets reality

Abstract: In this review we focused our attention on sulfur mustard [bis(2-chloroethyl) sulphide], the main vesicant chemical warfare agent (CWA), which has been widely used in different military conflicts, including World War I and the Iran-Iraq war. Moreover, the evolution of the recent Iraq and Syria conflicts suggests that terrorist groups are aware of the significant psychological and media effects that would be produced by the mere attempt to use CWAs. Sulfur mustard can produce the alkylation of macromolecules be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…The melatonin cascade also enables extremely efficient electron transfer [80] to scavenge most RONS [25,53,81,82] and the ONOO - [83,84]. In addition, genomic regulation exerted by melatonin modulates pro-oxidant and antioxidant mechanisms and mitochondrial metabolism [85,86], therefore enhancing cellular responses against DNA alteration and chemical damage [51,[87][88][89]. This multidimensional response of melatonin towards the repair of modified sites, the elimination of macromolecule damaging agents and the activation of antioxidative defense gives it proficiency to neutralize mustard pathology.…”
Section: Role Of Melatonin In Counteracting Sulfur and Nitrogen Musta...mentioning
confidence: 99%
“…The melatonin cascade also enables extremely efficient electron transfer [80] to scavenge most RONS [25,53,81,82] and the ONOO - [83,84]. In addition, genomic regulation exerted by melatonin modulates pro-oxidant and antioxidant mechanisms and mitochondrial metabolism [85,86], therefore enhancing cellular responses against DNA alteration and chemical damage [51,[87][88][89]. This multidimensional response of melatonin towards the repair of modified sites, the elimination of macromolecule damaging agents and the activation of antioxidative defense gives it proficiency to neutralize mustard pathology.…”
Section: Role Of Melatonin In Counteracting Sulfur and Nitrogen Musta...mentioning
confidence: 99%
“…(iv) Bacterial skin infections by mustard exposure may be prevented by the antimicrobial effect of melatonin [ 35 ]. Therefore, after mustard exposure, the melatonin supplementation may not only reduce the oxidative damage and alkylation of cellular macromolecules [ 36 ] but also improve the cutaneous regenerative potential [ 37 ].…”
Section: Target Organs and Acute Toxicity Of Blister Agents: Focus On Melatonin Therapy And Safety Profilementioning
confidence: 99%
“…Previously, our research group reported through computational calculations the hydrogen-atom transfer (HAT) as the suitable mechanism to quench SM, furnishing the much less toxic thiirane [ 36 , 101 ]. The recognized free radical scavenging capacity of melatonin also facilitates the neutralization of mechlorethamine-induced toxic damage.…”
Section: Reaction Mechanisms Of Melatonin With Blistering Agents (Hat Mechanism and Counteract Dna Damage)mentioning
confidence: 99%